ANALISIS MANAJEMEN PELAYANAN DAN PENINGKATAN MUTU PENDIDIKAN INKLUSI BERDASARKAN TEORI DIFFERNTIATED OF INSTRUCTION DI SEKOLAH DASAR NEGERI PLUMUTAN KABUPATEN SEMARANG TAHUN 2023 - Lailatul Azizah, Nova; Purwati, Panca Dewi; Sismulyasih, Nugraheti (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
Education or schools that accept all children regardless of their potential, physical, mental, socio-emotional condition, religion, gender, or economic background. It is an educational service for children with special needs regardless of their physical, intellectual, social, emotional, and other conditions to learn together with normal children in regular schools, commonly known as inclusive education. Aligned with the theory of Differentiated Instruction, which explains that every child can learn in one class according to their varying abilities. This research aims to describe the service and quality improvement in implementing inclusive education at SD. This research uses a qualitative method with a descriptive approach. Data collection is done using interview, observation, and documentation instruments. The results of this study show that the planning, implementation, and evaluation of inclusive education learning are done by balancing the abilities of learners, especially children with special needs. The implementation of inclusive education at SD Plumutan aligns with the theory of Differentiated Instruction.